Ranching of sea cucumber in Indonesia : A study case of Holothuria atra. Issue 1 (May 2021) - Hartati, R; Zainuri, M; Ambariyanto, A; Widianingsih, W; Mustagpirin,; Panji, F
Abstract: Sea ranching is one of the promising sustainable ways to restore depleted stocks and increase production of sea cucumber. Before, only high price species were exploited but now the demand is extended to many other low-value species, such as Teripang Hitam, H. atra . The present work were aimed to observed the growth and survival of H. atra ranching using pen system. Sea pens system size of 5meter x 5meter x 1.8meter was set up in Teluk Awur Waters, Jepara, Indonesia. They were designed as mesocosms that mimic sea ranching location. Wild young H. atra (average weight of 100 g) from Panjang Island, located adjacent to Teluk Awur waters were stocked at 3 individu.m −2, reared for five months without food addition. Sea cucumber was weighed and counted monthly to determine their growth and survival rate. The results of present experiment revealed that sea cucumber increased their weight with the time of rearing, the average weight gain and survival rates were 212 g and 83% respectively. It showed that their adaptation to the new environment was went well. The sea cucumber got intake of food that naturally grew in the sea pens or transported by the sea current from surrounding area. This result showed promising application on sea ranching for marine natural conservation.